DIGITALISASI PENCATATAN PENJUALAN SEBAGAI UPAYA MENINGKATKAN TRANSPARANSI KEUANGAN PADA TOKO ERNAMA KOSMETIK - Parwati, Nika Parwati; Asmara Yanti , Ni Nyoman Suli Asmara Yanti (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
ABSTRACT This study aims to describe the implementation process of a digital sales recording system and its impact on financial transparency and efficiency at Toko ERnama Kosmetik. Before adopting the digital system, all transaction records were manually documented using notebooks and handwritten receipts, which often led to recording errors, delayed reporting, and difficulties in tracking sales data. This research employs a descriptive qualitative approach, using observation, in-depth interviews, and documentation to collect data related to the store’s operational activities. The results indicate that the implementation of an application-based sales recording system significantly improves the efficiency and accuracy of financial documentation. Data compilation becomes faster, recording errors are reduced by more than 80%, and financial reports can be accessed automatically and in real time. Furthermore, the digital system enhances financial transparency and accountability since every transaction is systematically recorded and easily traceable. The study concludes that the digitalization of sales recording plays a crucial role in establishing a more professional, efficient, and data-driven management system for small and medium enterprises MSMEs Keywords: Digitalization, Financial Transparency, Information System, MSMEs, Sales Recordi